New recommendations for combating global food and nutrition security. (Research'eu results magazine)
By 2023, the world's population is due to hit 8 billion according to a recent UN survey. Finding a way to ensure that all those people and well-fed and well-nourished will be a major challenge of the 21st century. One EU-funded project has been working hard to provide the policy solutions to this challenge, emphasising the need for a robust and stable world food system that can cater for everyone's needs.